2023
DOI: 10.1002/advs.202301872
|View full text |Cite
|
Sign up to set email alerts
|

Cable‐Car Electrocatalysis to Drive Fully Decoupled Water Splitting

Abstract: The increasing demand for clean energy conversion and storage has increased interest in hydrogen production via electrolytic water splitting. However, the simultaneous production of hydrogen and oxygen in this process poses a challenge in extracting pure hydrogen without using ionic conducting membranes. Researchers have developed various innovative designs to overcome this issue, but continuous water splitting in separated tanks remains a desirable approach. This study presents a novel, continuous roll‐to‐rol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Interestingly, Wu and colleagues drew inspiration from the cable car model to develop a novel "cable-car" electrode (CCE) structure capable of uninterrupted hydrogen production from Ni(OH) 2 . 91 A schematic diagram of the device is shown in Fig. 10, wherein the transfer module is used to transfer CCEs so that the Ni(OH) 2 electrode alternates between hydrogen and oxygen tanks.…”
Section: In Alkaline Electrolytesmentioning
confidence: 99%
“…Interestingly, Wu and colleagues drew inspiration from the cable car model to develop a novel "cable-car" electrode (CCE) structure capable of uninterrupted hydrogen production from Ni(OH) 2 . 91 A schematic diagram of the device is shown in Fig. 10, wherein the transfer module is used to transfer CCEs so that the Ni(OH) 2 electrode alternates between hydrogen and oxygen tanks.…”
Section: In Alkaline Electrolytesmentioning
confidence: 99%
“…Membranes can occupy more than 24% volume in the case of a PEM in the electrolyzer stack. 54 Further, the cyclic stability of soluble RMs may limit the decoupling process, particularly as they are diffusing in solution and may find reactive pairs. In the next subsections, we describe ways to address such limitations with different strategies.…”
Section: Anodementioning
confidence: 99%
“…Long et al reported a similar device for decoupling HER and OER processes but used AE as a running cable car that cycles multiple AEs between the chambers (Figure 9). 54 The process worked with the application of an external voltage of at least 1.4 V for HER, and less than 0.9 V is applied for OER at 50 mA cm −2 . For 20 mA cm −2 , less than 0.5 V is required for OER.…”
Section: Soluble Redox Mediator With One Electrochemical and One Spon...mentioning
confidence: 99%
See 2 more Smart Citations